Desarrollo e implementación de los módulos de: inventario, compra, facturación, cartera integrados al sistema contable "Gesv" para la empresa "La mejor compra" utilizando Java y base de datos Postgresql - Villacreses Sarzoza, Eva Gabriela (2014)
This research design and implementation was carried out under an analysis of the problems presented by Best Buy Company located in the city of Machala, in the area of marketing their products. Especially those relating to billing, inventory, portfolio purchase. Since Best Buy Company does not have an accounting system which makes it difficult latest technology will make the transactions involved with these modules.